Wpływ globalnego kryzysu finansowego pierwszej dekady XXI w. na sytuację finansową domów i biur maklerskich w Polsce - Banaszczak-Soroka, Urszula (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
Among the capital market institutions very important role is played by subjects offering brokerage services. They are agents in deals which are made on stock exchanges. This function is the source of many duties for brokerage offi ces. Security of brokerage branch activity strongly infl uences stability of whole capital market, both in periods of slup and bull market. One of the factors in brokerage branch evaluation is its fi nancial situation measured with income and elements which are creating this income (outcome of brokerage, capital and investment activity). Experience of Polish market shows that not always brokerage activity has biggest share in the structure of whole outcome. Contrary it could be its little part what happened during 2007 slump. This fact can be disturbing regarding that MFID directive puts on brokerage branch many fi nancial restrictions which limits income from capital and investment activity
Keywords: hossa; bessa; firmy inwestycyjne; wyniki finansowe; domy maklerskie; kryzys gospodarczy